Consonant Repertoire of a Prelinguistically Deaf Child with Late-Mapping Cochlear Implants - Binos, Paris; Sfakianaki, Anna; Psillas, George K. (My University, 2021)
Objective: The present case study aims to report on the consonant repertoire during the pre-linguistic and first linguistic stage of a Greek-Cypriot speaking child bilaterally implanted with multichannel Cochlear Implants (CIs). Background: Children with Hearing Loss (HL) produce canonical babble later, and consonantal inventories of HL children are smaller. However, the consonant repertoire of CI Greek-speaking children has not been examined thus far and research on types of consonantal errors during phonological acquisition is scant. Clinical Case: A pre-linguistically deaf child (CY, 7;0 years old) received the first CI at 7 months of age, but the external part of the device was fitted at 2;7 years. An investigation of the child’s speech at 7;0 years was conducted through auditory analysis. The child’s canonical utterances were transcribed in IPA and his consonants were classified into subcategories, depending on articulation place, articulation manner and resonance. Regarding place, alveolar consonants were the main category produced. As regards manner, closed consonants was the first category to appear, while in terms of voicing, voiceless consonants were recorded more often than voiced ones. The analysis also showed that consonants /t/, /s/ and /p/ were dominant in the child’s speech and revealed several phonological processes. Conclusion: The present case holds special interest as the child’s phonological system is still between the pre-linguistic/first linguistic stages due to the delayed CI mapping. The results agree in part with several studies in the literature, while specific phonological error patterns observed, remain to be verified in other CI Greek-speaking children.
Keywords: Cochlear implant; Deaf; Prelinguistic; Consonants; Speech; Evaluation